Association of Dissociation with Suicide Attempt and Non-Suicidal Self Injury in Adolescents with a History of Sexual Abuse. Issue 1 (2nd January 2023) - Bikmazer, Alperen; Koyuncu, Zehra; Kavruk Erdim, Nese; Kadak, Muhammed Tayyib; Tarakcioglu, Mahmut Cem; Gokler, Enes; Gormez, Vahdet; Ozer, Omer Akil
Abstract : Objective : Dissociative symptoms are considered risk factors for suicide and non-suicidal self-injury (NSSI). In this study, the relationship between suicidal behaviors and NSSI with dissociative symptoms in adolescents with a history of Child Sexual Abuse (CSA) was investigated. Methods : A total of 100 adolescents with a history of CSA were evaluated with a detailed forensic psychiatric interview. Dissociative symptoms were measured with the self-report Adolescent Dissociative Experiences Scale (A-DES) and the parent-reported Child Dissociative Checklist (CDC). Results : While dissociative symptoms did not differ between adolescents with and without suicide attempts (CDC; p =  .068 and A-DES; p =  .060), they were significantly higher in adolescents with non-suicidal self-harming behavior (CDC; p <  .001 and A-DES; p =  .001). Suicide attempts and NSSI were more common in those who reported genital touching as a type of sexual abuse (respectively, p =  .003; p =  .048). In regression analysis; history of psychiatric treatment (OR = 9.09 [95% CI = 1.52, 54.29]) and NSSI (OR = 8.18 [95% CI = 2.01, 33.23]) were independently associated with suicide attempts. In addition, parent-reported dissociative symptoms (CDC scores) (OR = 1.27 [95% CI = 1.06, 1.53] and suicide attempt (OR = 8.09 [95%CI = 1.96, 33.42] showed independent association with NSSI. Conclusions : Dissociative symptoms may be predictive factors for NSSI and should be considered in risk assessment of adolescents with a history of CSA.